الدافع المعرفي وعلاقته بالاتجاه نحو مهنة التدريس لدى طلبة معهد التربية البدنية والرياضية بالأغواط - مجادى، مصطفى Majadi, Mustafa; ملياني، عبدالكريم; بن سعيد، محمود Bin Said, Mahmoud (جامعة زيان عاشور الجلفة - معهد علوم وتقنيات النشاطات البدنية والرياضية, 2020)
يهدف البحث إلى التعرف على العلاقة بين الدافع المعرفي ومهنة التدريس لمادة التربية البدنية الرياضية وخلصت الدراسة إلى أن هناك علاقة بين الرغبة في الاستزادة من المعلومات والمستوى المعرفي الثقافي، وبين المعالجة العملية للمعلومات وبين الاقتناع والرضا الذاتي، وبين ترحيب الطلبة بصعوبات البحث العلمي والبعد الاقتصادي لتوجههم المهني لطلبة لمعهد التربية البدنية والرياضية.
The research is aimed at identifying the relationship between the cognitive motive and the teaching profession of physical physical education, and the study concluded that there is a relationship between the desire to increase information and the cultural level of knowledge, between the practical treatment of information and between conviction and self-satisfaction, and between the students' welcoming the difficulties of scientific research and the economic dimension of their professional orientation towards the students of the Institute of Physical and Sports Education.
Keywords: الدافع المعرفى -- الاتجاه نحو مهنة التدريس -- طلبة معهد التربية البدنية والرياضية بالأغواط